A Pedagogical Approach to Qur'anic Literacy: Implementing the Baghdadiyah Method for New Students at Darul Falah V Islamic Boarding School - Zuhria, Farida; Arini, Aida (HEUTAGOGIA: Journal of Islamic Education, 2026)
This study aims to examine the implementation of the Baghdadiyah method in improving the Qur'an reading skills of new students at the Darul Falah V Islamic Boarding School in Cukir, Diwek, Jombang. The background of this study indicates that the Qur'an-reading skills of new students remain low, particularly in familiarity with the Hijaiyah alphabet, the articulation points of letters, reading fluency, and basic Tajwid. This study employed a descriptive qualitative approach using a case study design, incorporating observation, interviews, and documentation. The results indicate that the Baghdadiyah method was systematically implemented through the planning, implementation, and evaluation stages. During the planning stage, students were grouped by ability, teaching materials were developed, and lessons were prepared. The implementation stage was conducted in both group and individual settings using the "read-and-listen" technique, starting from letter recognition through to reading the Qur'an. The evaluation stage was conducted through reading tests and direct observation to assess reading fluency and accuracy. The research results indicate an improvement in the students' ability to read the Qur'an following the implementation of the Baghdadiyah method, particularly in reading fluency, the accuracy of letter articulation (makharijul huruf), and basic Tajwid. Supporting factors included adequate facilities and infrastructure, and the students' consistency, while inhibiting factors included student absenteeism, a lack of understanding of Tajwid, and differences in students' initial abilities. Thus, the Baghdadiyah method has proven effective in improving new students' ability to read the Qur'an in line with the Islamic boarding school's learning objectives.